Longitudinal Extensive Transverse Myelitis due to Varicella Zoster Virus Infection in a Patient without Immunodeficiency: A Case Report - Fettah Eren (Van Tip Dergisi, 2018)
Varicella zoster virus (VZV) is a virus belonging to the family of herpes virus that can remain latent in trigeminal nerve and dorsal root ganglia. Some neurological complications; encephalitis, myelitis, meningitis and central nervous system angiitis may occur with virus reactivation. These complications are very rare in people with normal immune response. A 70-year-old male patient presented with complaints of lower extremity weakness and incontinence for 2 days. Vesiculobullous lesions were observed in the area of the left lower extremity L5 dermatome and sacrum. Magnetic resonance imaging showed involvement of between T9 and T12 as transverse myelitis. Lymphocytic pleocytosis and protein elevation was detected in sample of the cerebrospinal fluid. VZV-DNA positivity determined in polymerase chain reaction (PCR). Patients with dermatomal lesions and myelitis findings should be considered transverse myelitis associated with VZV even if they have not immunodeficient. Rapid recognition and treatment are important for the prognosis.